La Banca Privada en el Crecimiento Económico de un país - Vásquez, Mario Enrique (2016)
If all countries with a developed, strong and smooth financial system contribute to the sustained development of the economy of a country, then the solution to the economic underdevelopment of the countries could be focused on governments to provide them the necessary assistance private banking. This study presented as private banks can help the economic growth of a country.